2017
DOI: 10.18433/j3805b
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Valganciclovir 900mg Versus 450mg for Cytomegalovirus Prophylaxis in Renal Transplantation: A Systematic Review and Meta-Analysis

Abstract: -Objectives:Valganciclovir 900 mg/day is approved for cytomegalovirus (CMV) prophylaxis, but 450 mg/day is seems also effective. We systematically reviewed the efficacy and safety of low-dose versus high-dose valganciclovir prophylaxis in renal transplantation recipients. Methods: An electronic search was conducted up to November 29, 2016. The primary outcomes were incidences of CMV, CMV disease, mortality and opportunistic infection. The second outcomes were acute rejection, allograft loss, adverse drug react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…We identified 5 published studies in intermediate-risk kidney transplant recipients: 3 involved 6-month prophylaxis, 8,10,14 and the other two involved 3-month prophylaxis, 12,13 one of which did not adjust for confounders. 13 All aforementioned reports indicated that the effectiveness of LD-VGC was at least comparable to that of SD-VGC prophylaxis, in agreement with our findings and those of two recent meta-analyses with direct or indirect comparisons between SD and LD-VGC prophylaxis, 9,17 one that focused specifically on intermediate-risk kidney transplant recipients. 17…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We identified 5 published studies in intermediate-risk kidney transplant recipients: 3 involved 6-month prophylaxis, 8,10,14 and the other two involved 3-month prophylaxis, 12,13 one of which did not adjust for confounders. 13 All aforementioned reports indicated that the effectiveness of LD-VGC was at least comparable to that of SD-VGC prophylaxis, in agreement with our findings and those of two recent meta-analyses with direct or indirect comparisons between SD and LD-VGC prophylaxis, 9,17 one that focused specifically on intermediate-risk kidney transplant recipients. 17…”
Section: Discussionsupporting
confidence: 89%
“…13 All aforementioned reports indicated that the effectiveness of LD-VGC was at least comparable to that of SD-VGC prophylaxis, in agreement with our findings and those of two recent meta-analyses with direct or indirect comparisons between SD and LD-VGC prophylaxis, 9,17 one that focused specifically on intermediate-risk kidney transplant recipients. 17…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, 2% acute rejection, 8% PTDM, 1% graft loss and 98% patient survival rates were observed in the low-dose group and no statistically significant difference was observed when compared to the high-risk patients 13 . In a recent meta-analysis, patients receiving low-dose and highdose valganciclovir were compared, and no statistically significant differences were observed with respect to CMV disease (p=0.36 for 1271 patients), acute rejection (p=0.19 for 1343 patients), graft loss (p=0.24 for 1271 patients), mortality (p=0.23 for 1271 patients), opportunistic infections (p=0.14 for 985 patients), and leukopenia (p=0.18 for 1082 patients) 14 . In our study, the rate of CMV disease was found to be 1.5% (n=1/68) in renal transplant recipients with low dose valganciclovir prophylaxis, similar to the rates in the literature 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Valganciclovir 450mg daily is also effective for CMV prophylaxis and is associated with lower risk for hematological side effects than the high dose (Gabardi et al, 2015;Halim et al, 2016;Heldenbrand et al, 2016;Stevens et al, 2015). According to a systematic review and meta-analysis, valganciclovir 900mg and 450mg daily dosing are equipotent for CMV prophylaxis in allrisk renal transplant recipients at least within the first year of transplantation with no differences regarding acute rejection, allograft loss, mortality, opportunistic infections, premature discontinuation of valganciclovir treatment and leukopenia (Xin et al, 2017). However, major concerns with the 450mg daily dose are higher risk of ganciclovir resistance and breakthrough infection among CMV donor-positive/recipient-negative (D+/R-) kidney transplant recipients (Gabardi et al, 2015;Stevens et al, 2015).…”
Section: Discussionmentioning
confidence: 99%